Hormone of darkness: Melatonin [Karanlıǧın hormonu: Melatonin] - (:unkn) unknown (Marmara University, 2010)
The hormone melatonin (5-methoxy-N-acetyltryptamine) is synthesized primarily in the pineal gland and retina, and in several peripheral tissues and organs. The endogenous rhythm of secretion is generated by the suprachiasmatic nuclei and entr ained by the light and dark cycle. It helps regulate other hormones and maintains the body's circadian rhythm. Melatonin is ubiquitously distributed and because of its small size and amphiphilic nature it is able to reach easily all cellular and subcellular compartments. It is a natural occurring compound with well-known antioxidant properties and has been proven as a powerful cytostatic drug in vitro as well as in vivo. The efficacy of melatonin has been assessed as a treatment of ocular diseases, blood diseases, gastrointestinal tract diseases, cardiovascular diseases, diabetes, rheumatoid arthritis, fibromyalgia, chronic fatigue syndrome, infectious diseases, neurological diseases, sleep disturbances, aging and depression. This review summarizes the pharmacokinetic properties and physiologic and pharmacological effects of melatonin.
Keywords: Antioxidant; Melatonin